STUDENT ARGUMENTATION SKILL ANALYSIS OF SOCIOSCIENTIFIC ISSUES IN SOLVING ENVIRONMENTAL PROBLEMS - Rita Istiana; Desti Herawatia (UNIVERSITAS PAKUAN, 2019)
This is a mixed method-explanatory research. This study aims to obtain information about the relationship between the ability to solve environmental problems with students 'argumentation skills about socio-scientific issues and the reasons why the variable ability to solve environmental problems has a very high relationship in improving students' argumentation skills about socio-scientific issues as well as other factors that influence it in addition to the ability to solve environmental issues. This research was conducted in November 2017 until May 2018. The population of this research is Biology Education Student, FKIP, Universitas Pakuan academic year 2017/2018. Sampling technique using purposive sampling and Slovin. The sample of 113 students consist of semesters 2 to semester 6. Based on the result of significance test and linearity test it can be concluded that simple regression analysis with equation Ŷ = 0,898 + 0,049 X is significant and linear. Based on the results of quantitative research obtained correlation coefficient (ry) between the ability to solve environmental problems with student argumentation skills about socio-scientific issues of 0.765. The value of this correlation coefficient shows that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, it means that the ability to solve the environmental problems contributes very highly to students' argumentation skill about socio-scientific issue. Based on the results of interviews on several sources, there are other factors that influence students' argumentation skill about socio-scientific issues among others, confidence, lecturer role, and peer role during discussion.